Approaches to retrospective conversion of catalogue records of libraries (2001)
This paper discusses the precedents to retrospective conversion It look at the genesis and development of Machine Readable format Emphasis is placed on through planning which should spell out the focus of the exercise; make provision for ,the right caliber of staff, provide the necessary funds; weigh and evaluate options and ensure management involvement in monitoring the project. The options to retrospective conversion are detailed and the methods for carrying out the exercise are specified